Pengaruh Beban Kerja dan Kompensasi terhadap Loyalitas Karyawan: Sensus pada Karyawan Bagian Pengiriman Paket Driver dan Rider Shopee Express di Kota Tasikmalaya - Ilham Ajie Saputra Wibawa; Barin Barlian; Nita Fauziah Oktaviani (CV. Ulil Albab Corp, 2023)
This study aims to determine the Effect of Workload and Compensation on Employee Loyalty (Census on Employees of the Shopee Express Driver and Rider Package Delivery Section in Tasikmalaya City). This study uses the census method. The type of data used is primary data and secondary data, with a research sample of 30 people, using the saturated sample method. The analytical tool used in this research is SPSS version 25. Data collection techniques used are interviews, questionnaires, and documentation studies. The results showed that workload and compensation simultaneously had a significant effect on employee loyalty. Workload partially has a significant effect on employee loyalty. Compensation partially has no significant effect on employee loyalty.